THE EFFECT OF PROBLEM BASED LEARNING ON LEARNING OUTCOMES ON HUMAN SKELETAL SYSTEM MATERIALS IN GRADE VIII - Anggi Anggana Josephine; Binari Manurung (Jurnal Pelita Pendidikan, 2023)
This research aims to know how the influence of problem-based learning models on student learning outcomes on the Human Skeletal System in grade VIII material of SMP N 14 Medan. This type of research is a quasi-experiment. The population in the study was all students of class VIII semester 1 of SMP Negeri 14 Medan consisting of 6 classes. The sample of this study was taken in two classes, namely VIII-1 as an experimental class of 30 people and class VIII-2 as a control class of 30 people determined by cluster random sampling. The instrument used is a learning outcomes test in the form of multiple choices consisting of 20 items. The hypothesis test used in this study is the t test. Based on the results of data analysis, the average score of the experimental class pretest was 49.0 and the average value of the control class pretest was 44.66 while the average score of the experimental class postest was 71.66 and the control class was 60.66. Based on the results of the t postes test, a calculation of > ttabel = 2,747 > 1,672 with α = 0.05 was obtained so that Ha was accepted and H0 was rejected. So it can be concluded that there is an effect of problem-based learning models on student learning outcomes on human skeletal system material in class VIII SMP N 14 Medan